2017
DOI: 10.1016/j.reprotox.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylated polychlorinated biphenyl metabolites (OH-PCBs), maternal smoking and size at birth

Abstract: In a sample of 442 births from the Child Health and Development Studies cohort, we examined associations between maternal prenatal exposure to hydroxylated polychlorinated biphenyl metabolites (OH-PCBs) and pregnancy outcomes, and whether associations were mediated by maternal thyroid hormone levels and/or modified by maternal smoking. Compared to nonsmokers, smokers had twice the mean concentration of 4-OH-CB107 (p<0.001) and lower levels of its parent compound, PCB118 (p=0.001). Among mothers who smoked, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…Intact PCBs are hardly excreted due to their strong hydrophobicity if only they are metabolized and conjugated to form more polar molecules . The presence of the −OH group makes OH-PCBs have a certain hydrophilic nature, leading to the elimination of OH-PCBs from the animal body through excretion. , As a rough estimate, there is nearly 10% of PCB 101 intake by laying hens from the feed that eliminated as a metabolic form of 4′-OH-PCB 101 via excretion. The concentration of 4′-OH-PCB 101 in excrement was similar to that in the yolk, whereas the dry matter weight of the excrement (about 30 g/d) was greater than that of egg yolk (about 9.4 g) produced by laying hen every day.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Intact PCBs are hardly excreted due to their strong hydrophobicity if only they are metabolized and conjugated to form more polar molecules . The presence of the −OH group makes OH-PCBs have a certain hydrophilic nature, leading to the elimination of OH-PCBs from the animal body through excretion. , As a rough estimate, there is nearly 10% of PCB 101 intake by laying hens from the feed that eliminated as a metabolic form of 4′-OH-PCB 101 via excretion. The concentration of 4′-OH-PCB 101 in excrement was similar to that in the yolk, whereas the dry matter weight of the excrement (about 30 g/d) was greater than that of egg yolk (about 9.4 g) produced by laying hen every day.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Animal experimental and epidemiological research indicates that the developing fetus is vulnerable to PCB exposure (Kezios et al, 2012; Allen et al, 1980). In utero exposure to PCBs has been linked to unfavorable birth outcomes such as decreased gestational length and reduce birth weight (Kezios et al, 2012; Govarts et al, 2012; Tang et al, 2018; Tatsuta et al, 2017; Nieuwenhuijsen et al, 2013; Kezios et al, 2017). Developmental PCB exposure has also been reported to result in long-term effects such as increased risk of breast cancer and extended time to pregnancy in daughters (Gennings et al, 2013; Cohn et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the discovery that PCBs can undergo hydroxylation through natural and anthropogenic means to form hydroxylated polychlorinated biphenyls (OH‐PCBs) has raised serious environmental concern because OH‐PCBs are known to be several orders of magnitude more toxic than the parent PCBs (Tehrani & Van Aken, 2014). Previous studies have shown that exposure of humans and animals to OH‐PCBs causes certain biological perturbations that are linked to the following downstream events and adverse outcomes: disruption of thyroid homeostasis, breast cancer, prolonged estrous cycle, decreased mental development index, low birth weight, alteration in steroid homeostasis, increased incidences of cervicovaginal track tumor, and increased levels of cardiometabolic risk factors (Berghuis et al, 2022; Dirinck et al, 2016; Kezios et al, 2017; Martinez et al, 2005; Meerts et al, 2004; Nomiyama et al, 2010; Park et al, 2009).…”
Section: Introductionmentioning
confidence: 99%